Positive electrode active material, positive electrode, and lithium secondary battery

By using secondary particles formed by lithium-based composite oxides with a single crystal structure and covering the cationic mixed layer on their surface, the problem of poor high-temperature stability of LiNiO2 in lithium secondary batteries is solved, and higher battery stability and safety are achieved.

CN119601651APending Publication Date: 2025-03-11ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411670191.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2020-11-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

LiNiO2 in lithium secondary batteries has poor high temperature stability, and when external pressure causes internal short circuit in a charged state, the positive electrode active material is prone to decompose itself, causing the battery to rupture and ignite.

Method used

The structural stability of the lithium composite oxide is optimized by preparing secondary particles formed by the condensation of primary particles of lithium-based composite oxide with a single crystal structure, and combining it with a cationic mixed layer on the surface of the particles.

Benefits of technology

The high temperature stability and storage stability of lithium secondary batteries are improved, and the possibility of side reactions between the positive electrode active material and the electrolyte is reduced, thereby preventing the battery from expanding and spontaneous decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601651A_ABST
    Figure CN119601651A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a positive electrode, and a lithium secondary battery, wherein the structural stability of a lithium composite oxide constituting the positive electrode active material is improved. The positive electrode active material according to the present invention comprises secondary particles in which a plurality of primary particles, which are lithium-based composite oxides, are aggregated, and the ratio of the average particle diameter of the secondary particles to the average particle diameter of the primary particles is 1.9-10.3. The Ni occupancy in the Li 3a site as determined by Rietveld analysis of X-ray diffraction of the secondary particles is greater than 0.53% and less than 6.44%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with a filing date of November 16, 2020, application number 202011280320.9, and invention name “Positive electrode active material and lithium secondary battery comprising the same”. Technical Field

[0002] The present invention relates to a positive electrode active material having improved structural stability of a lithium composite oxide constituting the positive electrode active material and a lithium secondary battery including the same. Background Art

[0003] Compared with other rechargeable battery systems, lithium secondary batteries have the advantages of high operating voltage, light weight, miniaturization, no memory effect, low self-discharge rate, long cycle life, and high energy density. Therefore, they are widely used in mobile phones, laptops, tablets and other mobile terminals.

[0004] In addition, in recent years, from the perspective of environmental protection, electric vehicles have been rapidly developed under the publicity of the government and automobile manufacturers, and lithium secondary batteries are considered to be the ideal power source for the next generation of electric vehicles due to their excellent performance.

[0005] Lithium-based composite oxides are used as positive electrode active materials for such lithium secondary batteries, among which lithium cobalt composite oxides (LiCoO) having high operating voltage and excellent capacity characteristics are mainly used. 2 ). However, LiCoO 2 Since the crystal structure is unstable due to delithiation, the high-temperature stability is poor and the battery is expensive, so there are limitations in its use as a power source in fields requiring large-capacity battery systems such as electric vehicles.

[0006] As a substitute for LiCoO 2 Materials for lithium manganese composite oxide (LiMnO 2 or LiMn 2 O 4 etc.), lithium iron phosphate (LiFePO 4 etc.) or lithium nickel composite oxide (LiNiO 2 Among them, lithium nickel composite oxide can realize large-capacity batteries due to its high reversible capacity of about 200 mAh / g, so it is more actively studied and developed.

[0007] However, compared with LiCoO 2 In comparison, LiNiO 2 The high temperature stability is poor, and if an internal short circuit occurs due to external pressure, etc. in the charging state, the positive electrode active material will decompose by itself, or the battery will rupture and catch fire due to side reactions between the interface and surface of the electrolyte and the positive electrode active material.

[0008] Therefore, it is necessary to develop a positive electrode active material that can maintain LiNiO 2 The excellent reversible capacity is improved while the high temperature stability is improved.

[0009] On the other hand, lithium secondary batteries can be classified into can type secondary batteries in which an electrode assembly is embedded in a metal can and pouch type secondary batteries in which an electrode assembly is embedded in a pouch made of a sheet such as an aluminum laminate, according to the shape of a battery case.

[0010] Pouch-type secondary batteries have the following advantages: light weight and low possibility of electrolyte leakage. The same number of secondary batteries can be achieved with a relatively small volume and mass. On the contrary, if the internal pressure of the battery box increases rapidly, there is a risk of explosion. Therefore, ensuring stability by controlling gas generation, which is the main reason for the increase in internal pressure of the battery box, is one of the important technical issues.

[0011] For example, when an overcurrent exceeding a limit flows through a secondary battery, the internal temperature of the battery rapidly rises, thereby causing a decomposition reaction of the electrolyte to generate gas, or gas is generated due to a side reaction between the interface and surface of the electrolyte and the positive electrode active material. Summary of the invention

[0012] Technical issues

[0013] The present invention aims to provide a method for maintaining LiNiO 2 A positive electrode active material having excellent reversible capacity while improving low thermal stability or structural stability and a lithium secondary battery comprising the same.

[0014] And, an object of the present invention is to provide a positive electrode active material and a lithium secondary battery including the same which can prevent battery swelling due to gas generation in a secondary battery by reducing the possibility of side reactions occurring between the interface and the surface of an electrolyte and the positive electrode active material.

[0015] Another object of the present invention is to provide a positive electrode active material capable of improving the structural stability of a lithium composite oxide by a cation mixed layer covering the surface of a primary particle, and a lithium secondary battery including the same.

[0016] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0017] Solutions to the problem

[0018] According to one aspect of the present invention, a positive electrode active material is provided, comprising secondary particles formed by agglomeration of a plurality of primary particles as a lithium-based composite oxide, wherein the ratio x2 / x1 of the average particle size x2 of the secondary particles to the average particle size x1 of the primary particles is greater than 1.9 and less than 10.3, and the Ni occupancy in the Li 3a position obtained by Rietveld analysis of X-ray diffraction of the secondary particles is greater than 0.53% and less than 6.44%.

[0019] According to one aspect of the present invention, there is provided a positive electrode active material including a lithium-based composite oxide having a single crystal structure.

[0020] The positive electrode active material includes a cation mixed layer present on the surface of the lithium-based composite oxide, and the thickness (d1) of the cation mixed layer may be in the range of greater than 0.0008 and less than 0.0052 relative to the average particle size (x1) of the primary particles.

[0021] And, according to another aspect of the present invention, a positive electrode for a lithium secondary battery including the positive electrode active material is provided.

[0022] Furthermore, according to another aspect of the present invention, a lithium secondary battery including the positive electrode is provided.

[0023] Effects of the Invention

[0024] The surface of the lithium-based composite oxide and / or the secondary particles formed by agglomeration of at least two lithium-based composite oxides and the surface of the grain boundaries are regions where a side reaction may occur between the positive electrode active material and the electrolyte.

[0025] According to the present invention, the lithium-based composite oxide as the primary particles constituting the secondary particles has a single crystal structure, so that the occurrence of a side reaction between the positive electrode active material and the electrolyte can be reduced.

[0026] That is, the high temperature stability and storage stability of the positive electrode active material can be improved by reducing the surface area and grain boundary surface of the lithium-based composite oxide and / or the secondary particles. By improving not only the high temperature stability of the positive electrode active material but also the storage stability, the gas generated by the positive electrode active material during the operation and / or storage of the positive electrode active material can be reduced.

[0027] Furthermore, according to the present invention, the cation mixed layer existing on the surface of the lithium composite oxide constituting the positive electrode active material satisfying the grain boundary density conditions defined herein can improve not only the structural stability of the lithium composite oxide but also the structural stability of the positive electrode active material.

[0028] Specific matters for implementing the invention will be described below, and specific effects of the present invention and the above-mentioned effects will be described. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figures 1 to 3 FIG. 1 is a schematic diagram schematically showing a cross section of a secondary particle that may be included in a positive electrode active material according to various embodiments of the present invention.

[0030] Figure 4 and Figure 5 The cross-sectional SEM images of the positive electrode active materials according to Example 1 and Example 2 respectively show the measurement results of the grain boundary density of the secondary particles included in the positive electrode active materials.

[0031] Figure 6 is a cross-sectional SEM photograph of the positive electrode active material according to Comparative Example 1, which shows the measurement result of the grain boundary density of the secondary particles included in the above positive electrode active material.

[0032] Figures 7 to 12 The following are SEM photos of the positive electrode active materials according to Example 1, Example 3, Example 4, Example 5, Example 7 and Example 11 respectively.

[0033] Fig.13 and Fig.14 The SEM images of the positive electrode active materials according to Comparative Example 1 and Comparative Example 2 are respectively.

[0034] Figures 15 to 20 The following are TEM images of the positive electrode active materials according to Example 1, Example 3, Example 4, Example 5, Example 7 and Example 11, respectively.

[0035] Fig.21 and Fig. 22 TEM images of the positive electrode active materials according to Comparative Example 1 and Comparative Example 2, respectively. DETAILED DESCRIPTION

[0036] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, the scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs. In addition, unless the context requires otherwise, the terms in the singular form shall include the plural form and the terms in the plural form shall include the singular form.

[0037] Terminology

[0038] The term "lithium-based composite oxide" as used herein is an oxide capable of occluding and releasing lithium ions, which includes lithium and metal elements, and in particular, the lithium-based composite oxide as used herein may be a lithium-nickel-based composite oxide containing lithium and nickel. In addition, the term "lithium-based composite oxide" as used herein may be defined as a primary particle constituting a positive electrode active material.

[0039] As used herein, the term "single crystal" refers to a crystal in a state where no grains or grain boundaries are included in the interior of the particle. In addition, the term "primary particle" used herein refers to a particle that exists alone and does not form an agglomerate. Therefore, a "lithium-based composite oxide having a single crystal structure" refers to a particle in a state where a primary particle composed of a lithium-based composite oxide is formed by a plurality of grains or does not contain a grain boundary in the interior of the primary particle.

[0040] As used herein, the term "secondary particle" refers to a primary particle itself as the above-mentioned lithium-based composite oxide or a particle formed by agglomerating at least two primary particles. In this case, secondary particles consisting of a single primary particle and / or secondary particles formed by agglomerating at least two primary particles can coexist in the positive electrode active material. When at least two primary particles are agglomerated to form a secondary particle, there is a grain boundary or grain boundary surface formed at the interface of the two primary particles in the secondary particle.

[0041] The term "grain boundary density" as used in this article refers to the number of grain boundaries or grain boundary surfaces formed as a result of the presence of at least two primary particles in a secondary particle. The more primary particles there are in the secondary particles, the greater the grain boundary density; the fewer primary particles there are in the secondary particles, the smaller the grain boundary density.

[0042] In this paper, the grain boundary density can be calculated by the following formula.

[0043] Grain boundary density = (number of interfaces between primary particles in secondary particles / number of primary particles constituting secondary particles)

[0044] When the number of primary particles present in the secondary particles is 1, the grain boundary density calculated according to the above formula is 0, and when the number of primary particles present in the secondary particles is 3 or more, the grain boundary density calculated according to the above formula is greater than 0.5.

[0045] On the other hand, in this article, the secondary particle can be a particle composed of a single primary particle having a single crystal structure, but is not limited thereto. That is, in this article, the secondary particle can be understood as a particle composed of a single single crystal particle or formed by agglomerating at least two single crystal particles. The definition of the above secondary particles is more clearly explained by the definition of the positive electrode active material described below.

[0046] The term "positive electrode active material" as used in this article is a broad concept that includes the above-mentioned secondary particles. A single secondary particle itself can be a positive electrode active material, but in this article, an aggregate of multiple secondary particles with the same and / or different grain boundary densities can be defined as a positive electrode active material.

[0047] Therefore, in the definition of the positive electrode active material to be described below, the description of the secondary particles having the aggregate characteristics of multiple secondary particles and the description of the secondary particles constituting the above positive electrode active material and the primary particles constituting the above secondary particles need to be understood separately.

[0048] Next, the positive electrode active material according to the present invention and the lithium composite oxide described above will be described in further detail.

[0049] Positive electrode active material

[0050] The grain boundary surface defined by the surface area of ​​the secondary particles included in the positive electrode active material and the primary particles present in the secondary particles is an area where side reactions may occur between the interface and the surface of the positive electrode active material and the electrolyte. The grain boundary surface defined by the primary particles present in the secondary particles can be understood as the interface between two adjacent primary particles, for example.

[0051] At this time, the thermal stability of the positive electrode active material can be improved and problems caused by the instability of the positive electrode active material (for example, reduced storage stability such as gas generation) can be prevented or alleviated by reducing the surface area of ​​the secondary particles and the grain boundary surface defined by the primary particles in the secondary particles.

[0052] A positive electrode active material for a lithium secondary battery according to an embodiment of the present invention includes secondary particles composed of primary particles of a lithium-based composite oxide having a single crystal structure.

[0053] In particular, the surface area of ​​the primary particles in the secondary particles and the grain boundary surface divided by the primary particles in the secondary particles can be reduced by making the primary particles constituting the secondary particles have a single crystal structure. Furthermore, the primary particles constituting the secondary particles have an isotropic lithium ion diffusion path in the long axis direction, so that the lithium ions in the secondary particles are concentrated in one direction instead of being diffused in multiple directions, thereby improving the lithium ion conductivity in the secondary particles.

[0054] Figures 1 to 3 A cross section of a secondary particle that may be included in a positive electrode active material according to various embodiments of the present invention is schematically illustrated.

[0055] like Figures 1 to 3The secondary particles 110, 120, 130 included in the positive electrode active material shown are formed by agglomerating 1 to 10 primary particles 111, 121, 131, and therefore have a relatively small surface area compared to secondary particles formed by agglomerating tens to hundreds of primary particles, thereby reducing the surface area where side reactions with the electrolyte occur. In addition, the number of primary particles forming the secondary particles is small, so the density of the grain boundaries is small, thereby also reducing side reactions on the grain boundary surfaces in the secondary particles.

[0056] Furthermore, according to the present invention, the probability that the primary particles constituting the plurality of secondary particles contained in the positive electrode active material have isotropic lithium ion diffusion paths in the long axis direction is increased. As described above, as the ratio of isotropic lithium ion diffusion paths in the long axis direction in the secondary particles increases, the lithium ion conductivity and the electronic lithium ion conductivity through the positive electrode active material can be improved.

[0057] In one embodiment, the positive electrode active material according to the present invention may be an aggregate of secondary particles having the same or different grain boundary densities.

[0058] In this paper, the grain boundary density can be calculated by the following formula.

[0059] Grain boundary density = (number of interfaces between primary particles in secondary particles / number of primary particles constituting secondary particles)

[0060] Secondary particles with different grain boundary densities can have different physical and chemical properties. Physical properties that vary according to different grain boundary densities include, for example, differences in surface area of ​​the secondary particles before and after pressing, and chemical properties that vary according to different grain boundary densities include, for example, differences in side reaction ratios between the surface and / or interface of the secondary particles and the electrolyte.

[0061] Specifically, the ratio of secondary particles having a grain boundary density of 0.5 or less among the plurality of secondary particles constituting the positive electrode active material according to the present invention may be 30% or more, preferably 50% or more, and more preferably 70% or more.

[0062] For example, when the secondary particle is composed of a single primary particle with a single crystal structure, the grain boundary density is 0 (the number of interfaces between primary particles in the secondary particle = 0 / the number of primary particles constituting the secondary particle = 1); when the secondary particle is composed of two primary particles with a single crystal structure, the grain boundary density is 0.5.

[0063] That is to say, the fewer the number of interfaces between primary particles in the secondary particles, the smaller the grain boundary density value will be. At this time, when the number of primary particles constituting the secondary particles increases, the number of interfaces between primary particles in the secondary particles also increases. Therefore, in order to make the grain boundary density below 0.5, the secondary particles need to be composed of a single primary particle with a single crystal structure or composed of two primary particles with a single crystal structure.

[0064] For example, the positive electrode active material according to the present invention may include secondary particles composed of 1 to 2 primary particles (hereinafter referred to as "first agglomerates" for convenience), secondary particles composed of 3 to 6 primary particles (hereinafter referred to as "second agglomerates" for convenience), and secondary particles composed of 7 to 10 primary particles (hereinafter referred to as "third agglomerates" for convenience).

[0065] In such Figure 1 In the first agglomerate 110 shown, the number of primary particles 111 that form secondary particles is 1 or 2. Compared with the second agglomerate and the third agglomerate, the number of primary particles that form secondary particles is smaller, so it has a relatively small surface area, thereby reducing the area where side reactions with the electrolyte occur.

[0066] Furthermore, the number of grain boundary surfaces b formed by the primary particles 111 in the first aggregate 110 may be one or less. Therefore, the probability of a side reaction between the grain boundary surfaces and the electrolyte is reduced compared to a case where the number of grain boundary surfaces is two or more.

[0067] The content of the first agglomerates is preferably 30% or more in the aggregates of secondary particles constituting the positive electrode active material. The ratio (%) of the first agglomerates in the aggregates of secondary particles refers to the ratio (%) of the number of first agglomerates to the total number of secondary particles constituting the aggregates.

[0068] If the ratio of the first agglomerate in the aggregate of the secondary particles constituting the positive electrode active material is less than 30%, the ratio of the first agglomerate in the aggregate is reduced, thereby increasing the average surface area and grain boundary density of the secondary particles constituting the positive electrode active material. As a result, the possibility of a side reaction between the positive electrode active material and the electrolyte increases, which may reduce the high temperature stability and storage performance of the positive electrode active material.

[0069] On the other hand, if the calcination temperature is increased, the ratio of the first aggregate in the aggregate of the secondary particles constituting the positive electrode active material can be increased. However, if the calcination temperature is too high, the possibility of deterioration of the positive electrode active material increases.

[0070] And, in such Figure 2In the second agglomerate 120 shown, the number of primary particles 121 forming secondary particles is 3 to 6, and the above-mentioned second agglomerate 120 can be present in the aggregate of secondary particles constituting the positive electrode active material at a content of less than 70%, preferably, more than 20% and less than 70%.

[0071] And, in such Figure 3 In the third agglomerate 130 shown, the number of primary particles 131 forming secondary particles is 7 to 10. Preferably, the third agglomerate 130 is present in an amount of 10% or less in the aggregate of secondary particles constituting the positive electrode active material.

[0072] At this time, the positive electrode active material may also include secondary particles formed by agglomerating a larger number of primary particles than the third agglomerate (secondary particles having 7 to 10 primary particles constituting the secondary particles). In this case, the ratio of the third agglomerate to the secondary particles formed by agglomerating a larger number of primary particles than the third agglomerate in the aggregate of the secondary particles is also preferably 10% or less.

[0073] When the ratio of the first aggregate is 70% and the ratio of the second aggregate is reduced to less than 20%, as a result, the ratio of the second aggregate relative to the third aggregate is reduced, and therefore, the average surface area and grain boundary density of the secondary particles constituting the positive electrode active material are increased, which can be a reason for reducing the high temperature stability and storage properties of the positive electrode active material.

[0074] On the other hand, when the ratio of second agglomerates in the aggregates of secondary particles constituting the positive electrode active material exceeds 30%, the ratio of second agglomerates relative to the first agglomerates is relatively large, and therefore, similarly, the average surface area and grain boundary density of the secondary particles constituting the positive electrode active material will increase.

[0075] Furthermore, the average particle size of the primary particles of the lithium-based composite oxide having a single crystal structure is preferably 1.0 μm to 5.0 μm. By making the average particle size of the primary particles of the lithium-based composite oxide having a single crystal structure within the range of 1.0 μm to 5.0 μm, the optimal density of the positive electrode active material formed by the above-mentioned lithium-based composite oxide can be achieved, and the effect of improving the structural stability of the cation mixed layer described below can be maximized.

[0076] Furthermore, the average particle size of the secondary particles may vary depending on the number of agglomerated primary particles, but may be 1.0 μm to 20.0 μm. Preferably, the secondary particles may include small secondary particles and large secondary particles, the small secondary particles may have an average particle size of 1.0 μm to 5.0 μm, and the large secondary particles may have an average particle size of 10.0 μm to 20.0 μm. Thus, the average particle size of the aggregate of the secondary particles formed by mixing the small secondary particles and the large secondary particles may be 3.0 μm to 18.0 μm.

[0077] As described above, the positive electrode active material according to the present invention can be an aggregate of secondary particles having the same or different grain boundary densities, and can also be an aggregate of small secondary particles and large secondary particles having different average particle sizes. The structural stability of the positive electrode active material can be improved by the aggregate properties of the secondary particles, and further, the high temperature stability and storage stability of the lithium secondary battery using the positive electrode active material can be improved.

[0078] The lithium-based composite oxide constituting the positive electrode active material according to the present invention may be represented by Chemical Formula 1 below.

[0079] [Chemical formula 1]

[0080] Li a Ni 1-(b+c+d+e) Co b M1 c M2 d M3 e O f

[0081] Among them, M1 is Mn or Al, M2 and M3 are independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb and Zr, and M1 to M3 are different metals (0.90≤a≤1.05, 0≤b≤0.20, 0≤c≤0.20, 0≤d≤0.05, 0≤e≤0.05, 1.0≤f≤2.0).

[0082] At this time, M3 is a metal different from M1 and can be added as a flux when preparing the lithium-based composite oxide represented by Chemical Formula 1. The flux plays a role in lowering the melting point to promote particle growth, thereby inducing the formation of a cation mixed layer described below at an appropriate ratio.

[0083] Also, the positive electrode active material according to the present invention may include a cation mixed layer present on the surface of the lithium-based composite oxide represented by Chemical Formula 1 above.

[0084] Specifically, the positive electrode active material may include primary particles of the lithium-based composite oxide having a single crystal structure and secondary particles formed by agglomerating the primary particles, and the cation mixed layer may exist on the surface of at least one selected from the primary particles and the secondary particles.

[0085] At this time, the cation mixed layer may include a composite oxide represented by the following Chemical Formula 2, and the composite oxide represented by the following Chemical Formula 2 is an oxide different from the lithium-based composite oxide represented by the above Chemical Formula 1.

[0086] [Chemical formula 2]

[0087] Li g Ni 1-(h+i+j+k) Co h M4 i M5 j M6 k O l

[0088] Among them, M4 is Mn or Al, M5 and M6 are independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb and Zr, and M4 to M6 are different metals (0.0≤g≤1.05, 0≤h≤0.20, 0≤i≤0.20, 0≤j≤0.05, 0≤k≤0.05, 1.0≤l≤2.0).

[0089] The cation mixed layer including the composite oxide represented by Chemical Formula 2 exists on the surface of the lithium-based composite oxide, thereby improving the structural stability of the lithium-based composite oxide as a primary particle.

[0090] More specifically, the composite oxide included in the cation mixed layer may be represented by Chemical Formula 3 below.

[0091] [Chemical formula 3]

[0092] Li m Ni n O l

[0093] (0.0≤m≤0.5,0.0 <n≤1,1.0≤l≤2.0).

[0094] The composite oxide contained in the cation mixed layer has a crystal structure selected from a layered structure, a rock salt structure and a spinel structure, or may have a crystal structure mixed with a composite oxide having at least one crystal structure selected from a layered structure, a rock salt structure and a spinel structure. However, in this case, preferably, the composite oxide contained in the cation mixed layer has a crystal structure different from that of the lithium-based composite oxide represented by the above chemical formula 1.

[0095] The thickness of the cation mixed layer on the surface of the lithium-based composite oxide as the primary particle constituting the positive electrode active material may be 0.24 nm to 12.03 nm, and the ratio of the thickness of the cation mixed layer to the average particle size of the primary particle may be greater than 0.0008 and less than 0.0052.

[0096] When the ratio of the thickness of the cation mixed layer to the average particle size of the primary particles is 0.0008 or less, the effect of improving the structural stability of the lithium-based composite oxide by the cation mixed layer is insufficient. On the other hand, when the ratio of the thickness of the cation mixed layer to the average particle size of the primary particles is 0.0052 or more, the thickness of the cation mixed layer becomes too large, and thus the electrical properties of the lithium-based composite oxide may be deteriorated.

[0097] Furthermore, the cationic mixed layer may also exist on the surface of the secondary particles. At this time, it can be confirmed that the ratio (d2 / x2) of the thickness (d2) of the cationic mixed layer relative to the average particle size (x2) of the secondary particles is greater than 0.00014 and less than 0.00281.

[0098] When the ratio of the thickness of the cation mixed layer to the average particle size of the secondary particles is 0.00014 or less, the effect of improving the structural stability of the secondary particles by the cation mixed layer is insufficient. On the other hand, when the ratio of the thickness of the cation mixed layer to the average particle size of the secondary particles is 0.00281 or more, the thickness of the cation mixed layer becomes too large, so the electrical properties of the secondary particles may be deteriorated.

[0099] On the other hand, the thickness of the cation mixed layer present on the surface of the secondary particles may be greater than the thickness of the cation mixed layer present on the surface of the primary particles. In this case, the electrical properties of the positive electrode active material can be improved within the range of not reducing the structural stability of the positive electrode active material composed of the primary particles and the secondary particles formed by agglomerating the primary particles.

[0100] At this time, preferably, the ratio (d1 / d2) of the thickness (d1) of the cation mixed layer present on the surface of the primary particle and the thickness (d2) of the cation mixed layer present on the surface of the secondary particle is greater than 0.53 and less than 1.0.

[0101] As described above, when the above-mentioned cation mixing layer exists on the surface of the above-mentioned primary particle and the above-mentioned secondary particle, respectively, the thickness of the above-mentioned cation mixing layer existing on the surface of the above-mentioned secondary particle is larger than the thickness of the above-mentioned cation mixing layer existing on the surface of the above-mentioned primary particle, thereby minimizing the degradation of the electrical properties of the positive electrode active material including the above-mentioned primary particle and the above-mentioned secondary particle, and at the same time, the structural stability effect caused by the above-mentioned cation mixing layer can be improved.

[0102] In the positive electrode active material according to various embodiments of the present invention, improved electrochemical characteristics and structural stability can be presented by making the ratio (d1 / x1) of the thickness of the cation mixing layer relative to the average particle size (x1) of the primary particle, the ratio (d2 / x2) of the thickness of the cation mixing layer relative to the average particle size (x2) of the secondary particle, and the ratio (d1 / d2) of the thickness of the cation mixing layer (d1) present on the surface of the primary particle and the thickness of the cation mixing layer (d2) present on the surface of the secondary particle within the predetermined range as described above.

[0103] In addition, the Ni occupancy rate in the Li 3a position obtained by Rietveld analysis of the X-ray diffraction of the secondary particles may be greater than 0.53%, preferably, greater than 1.0%, and more preferably, greater than 1.3%. Furthermore, the Ni occupancy rate in the Li 3a position of the secondary particles is preferably less than 6.44%. The Ni 3b position 3+ Ni is thermodynamically stable in the high temperature range. 2+ exists in the form of, at this time, Ni 2+ The size and Li + Similar, so it can occupy Ni 3+ 3a position.

[0104] Among them, the positive electrode active material according to the present invention has a Ni occupancy rate of 0.9% or more at the 3a position of the secondary particle, and it can be inferred that the cation mixed layer effectively exists on the surface of the secondary particle.

[0105] As described above, the positive electrode active material according to the present invention can improve structural stability through the cation mixed layer, thereby improving thermal stability and storage stability of the positive electrode active material.

[0106] When a positive electrode for a lithium secondary battery is prepared using a positive electrode active material, a slurry containing the positive electrode active material is coated on a positive electrode collector and then subjected to a drying and calendering (pressing) process. In particular, a positive electrode with a high energy density can be prepared by calendering under high pressure conditions. At this time, as the calendering density increases, the particles of the positive electrode active material with a small particle strength collapse, so the desired electrical properties cannot be expected. On the contrary, the positive electrode active material with a large particle strength can also maintain performance under high pressure calendering conditions without particle collapse.

[0107] In particular, when the particles collapse under calendering conditions, the ratio of secondary particles contained in a relatively small particle size distribution range increases. The change rate of the particle size distribution before and after pressing of the positive electrode active material according to the present invention is only 13% when pressed at 4.5 tons, and the change rate of the particle size distribution before and after pressing at 6 tons is only 26%. Therefore, even under high pressure calendering conditions, the positive electrode active material according to the present invention can maintain performance while minimizing the collapse of the particles.

[0108] Lithium secondary battery

[0109] According to another aspect of the present invention, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector may be provided, wherein the positive electrode active material layer may include the lithium composite oxide according to various embodiments of the present invention as a positive electrode active material.

[0110] Therefore, detailed description of the lithium composite oxide will be omitted, and only the remaining components not described above will be described below. In addition, below, the above lithium composite oxide is referred to as a positive electrode active material for convenience.

[0111] The positive electrode collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and examples thereof may include: stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector may generally have a thickness of 3 μm to 500 μm, or the adhesion of the positive electrode active material may be increased by forming micro-concave and convex on the surface of the collector. For example, various forms such as films, sheets, boxes, nets, porous materials, foams, and non-woven fabrics may be used.

[0112] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition on the positive electrode current collector. The positive electrode slurry composition includes the positive electrode active material and a conductive material, and optionally includes a binder as required.

[0113] The content of the positive electrode active material may be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt %, relative to the total weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, the positive electrode active material may have excellent capacity characteristics, but the present invention is not necessarily limited thereto.

[0114] The above-mentioned conductive material is used to provide conductivity to the electrode, and can be used without limitation, as long as it has electronic conductivity and does not cause chemical changes in the assembled battery. Specific examples thereof may include: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum or silver; conductive whiskers such as zinc oxide whiskers, potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and these substances can be used as a single one or as a mixture of two or more. The content of the above-mentioned conductive material can be 0.1 wt% to 15 wt% relative to the total weight of the positive electrode active material layer.

[0115] The above-mentioned binder serves to adhere the positive electrode active material particles to each other and improve the adhesion of the positive electrode active material and the collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, etc., and these substances can be used as a single or as a mixture of two or more. Relative to the total weight of the positive electrode active material layer, the content of the above-mentioned binder can be 0.1% by weight to 15% by weight.

[0116] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared using a common positive electrode preparation method. Specifically, the above-mentioned positive electrode can be prepared by coating a positive electrode slurry composition prepared by dissolving or dispersing the above-mentioned positive electrode active material and a selective binder and a conductive material in a solvent onto a positive electrode collector, and then drying and rolling the obtained product.

[0117] The above-mentioned solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and these substances may be used alone as a substance, or as a mixture of two or more. Considering the coating thickness and preparation yield of the slurry, as long as the above-mentioned solvent can dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and has a viscosity sufficient to obtain excellent thickness uniformity when it is used to prepare the positive electrode coating thereafter, the amount of the solvent used is sufficient.

[0118] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a film obtained by peeling off the support on a positive electrode collector.

[0119] In addition, according to another aspect of the present invention, an electrochemical device including the positive electrode may be provided. The electrochemical device may be specifically a battery, a capacitor, etc., and more specifically, may be a lithium secondary battery.

[0120] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode positioned opposite to the positive electrode, and a separator and an electrolyte between the positive electrode and the negative electrode. Since the positive electrode is the same as the positive electrode described above, a detailed description will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0121] The lithium secondary battery may further include a battery container for accommodating an electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member for sealing the battery container.

[0122] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0123] The above-mentioned negative electrode collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and examples thereof may include: copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel, aluminum-cadmium alloy, etc., whose surface is treated with carbon, nickel, titanium, silver, etc. In addition, the negative electrode collector may generally have a thickness of 3 μm to 500 μm, or, like the positive electrode collector, may increase the adhesion of the negative electrode active material by forming tiny concave-convex shapes on the surface of the above-mentioned collector. For example, various forms such as films, sheets, boxes, nets, porous materials, foams, and non-woven fabrics may be used.

[0124] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition on the negative electrode current collector. The negative electrode slurry composition includes the negative electrode active material and a conductive material, and optionally includes a binder as required.

[0125] The above-mentioned negative electrode active material can use a compound that can reversibly intercalate and deintercalate lithium. Specific examples thereof may include: carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber and amorphous carbon; metal compounds that can alloy with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; metal oxides that can be doped and dedoped with lithium such as SiOβ (0<β<2), SnO 2 , vanadium oxide and lithium vanadium oxide; or a composite containing a metal compound and a carbon compound such as a Si-C composite or a Sn-C composite, and any one of these substances or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, the carbon material can use both low-crystalline carbon and high-crystalline carbon. Low-crystalline carbon generally includes soft carbon and hard carbon, and high-crystalline carbon generally includes: amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, and high-temperature sintered carbon such as floating graphite (Kish graphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived coke (petroleum or coal tar pitch derived cokes).

[0126] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0127] The binder is a component that helps to bind the conductive material, the active material and the current collector, and its content is generally 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber and various copolymers thereof.

[0128] The above conductive material is a component for further improving the conductivity of the negative electrode active material, and the content of the conductive material can be 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. The above conductive material is not subject to any restrictions as long as it has conductivity and does not cause chemical changes in the battery, and conductive materials such as graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black can be used; conductive fibers such as carbon fibers or metal fibers; metal powders such as fluorocarbons, aluminum or nickel powders; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and polyphenylene derivatives.

[0129] In one embodiment, the negative electrode active material layer can be prepared by: coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material and a selective binder and a conductive material in a solvent on a negative electrode collector and drying the obtained product; or by casting the negative electrode slurry composition on a separate carrier and then laminating a film obtained by peeling off the carrier on the negative electrode collector.

[0130] On the other hand, in the above-mentioned lithium secondary battery, the separator separates the negative electrode and the positive electrode, and provides a migration channel for lithium ions, and there is no particular limitation, as long as it is generally used as a separator in a lithium secondary battery. In particular, a separator with low resistance to electrolyte ion migration and excellent ability to contain electrolyte liquid moisture is preferred. Specifically, it is possible to use: a porous polymer film, for example, a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure of more than two layers thereof. In addition, commonly used porous non-woven fabrics such as non-woven fabrics made of high melting point glass fibers or polyethylene terephthalate fibers can be used. In addition, in order to ensure heat resistance and mechanical strength, a coated separator comprising a ceramic component or a polymer material can also be used, and can be selectively used in a single-layer or multilayer structure.

[0131] In addition, the electrolyte used in the present invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used in the preparation of lithium secondary batteries, but the present invention is not limited thereto.

[0132] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0133] The above-mentioned organic solvent can be used without particular limitation as long as it can function as a medium through which ions participating in the electrochemical reaction of the battery can migrate. Specific examples of the organic solvent may include: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol or isopropanol; nitrile solvents such as R-CN (R is C 2 ~C 20 Straight chain, branched or cyclic hydrocarbon group, and may contain double bond aromatic ring or ether bond); amide such as dimethylformamide; dioxolane such as 1,3-dioxolane; sulfolane, etc. Among them, carbonate solvents are preferred, and a mixture of cyclic carbonates (such as ethylene carbonate, propylene carbonate, etc.) with high ion conductivity and high dielectric constant that can enhance the charging and discharging performance of the battery and low viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferred. In this case, mixing cyclic carbonates and chain carbonates in a volume ratio of about 1:1 to 1:9 can produce excellent electrolyte performance.

[0134] The above lithium salt can be used without particular limitation as long as it is a compound capable of providing lithium ions in a lithium secondary battery. Specific examples of the lithium salt may include LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 、LiCl、LiI、LiB(C 2 O 4 ) 2 The lithium salt may be advantageously used in a concentration range of 0.1 M to 2.0 M. When the lithium salt concentration is contained in the above range, the electrolyte has appropriate conductivity and viscosity, thereby being able to exhibit excellent electrolyte performance, and lithium ions can efficiently migrate.

[0135] In the above electrolyte, in order to increase the battery life property, inhibit the decline of battery capacity, improve the battery discharge capacity, etc., in addition to the above electrolyte forming components, one or more additives may be further included, including, for example: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride. Wherein, relative to the total weight of the electrolyte, the content of the above additives can be 0.1% by weight to 5% by weight.

[0136] The lithium secondary battery containing the positive electrode active material according to the present invention as described above stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore used in the following fields: the field of portable devices such as mobile phones, laptop computers and digital cameras; and the field of electric vehicles such as hybrid electric vehicles (HEV) and the like.

[0137] The shape of the lithium secondary battery according to the present invention is not particularly limited, but may have a cylindrical, angular, pouch or coin shape using a can. And, preferably, the lithium secondary battery can be used as a battery cell for a power source of a small device, and can also be used as a unit battery of a medium and large battery module including a plurality of battery cells.

[0138] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit battery and / or a battery pack including the same may be provided.

[0139] The battery module or the battery pack may be used in power tools (Power Tool); electric vehicles including electric vehicles (EV), hybrid vehicles and plug-in hybrid electric vehicles (PHEV); or as a power source for one or more medium and large devices in a system for storing electricity.

[0140] In particular, in the case of a pouch-type lithium secondary battery using a positive electrode including a positive electrode active material according to various embodiments of the present invention, there is less possibility of side reactions between the positive electrode active material and the electrolyte, thereby having the advantage of improving stability during storage and / or operation while reducing gas generation.

[0141] Therefore, in the case of a lithium secondary battery using a positive electrode including the positive electrode active material according to various embodiments of the present invention, for example, after being charged to 4.25 V at 0.2 C, the volume increase of the lithium secondary battery during storage at 60° C. for 14 days becomes 0.3 cm 3 The following ensures reliability and stability.

[0142] Hereinafter, the present invention will be described in more detail with reference to Examples. However, it should be understood that these Examples are only for the purpose of illustrating the present invention and should not be construed as limiting the scope of the present invention.

[0143] Preparation Example. Preparation of positive electrode active material

[0144] Example 1

[0145] In the NiCoAl(OH) prepared by coprecipitation reaction 2 (d(50) = 3.0 μm) and Li as a lithium compound 2 CO 3 After weighing and mixing with LiOH (Li / M ratio = 1.05 ± 0.05), a first heat treatment was performed at 800°C for 12 hours to prepare a Li 1.0 Ni 0.9 Co 0.078 Al 0.022 O 2 Lithium-based composite oxides.

[0146] The lithium-based composite oxide prepared above was added to distilled water and washed with water while maintaining the temperature. After the dehydration process, it was dried at 150° C. in a vacuum atmosphere. Next, the dried lithium-based composite oxide was subjected to a second heat treatment at 700° C. for 12 hours to obtain a positive electrode active material.

[0147] Example 2

[0148] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 850°C.

[0149] Example 3

[0150] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 900° C.

[0151] Example 4

[0152] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 730°C.

[0153] Example 5

[0154] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 750°C.

[0155] Example 6

[0156] In addition to further mixing 0.25 mol % of a barium-containing compound (Ba(OH) 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0157] Example 7

[0158] In addition to further mixing 0.3 mol % of a barium-containing compound (Ba(OH) 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0159] Example 8

[0160] In addition to further mixing 0.4 mol % of a barium-containing compound (Ba(OH) 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0161] Example 9

[0162] In addition to further mixing 0.3 mol % of a strontium-containing compound (Sr(OH) 2) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0163] Example 10

[0164] In addition to further mixing 0.05 mol % of a zirconium-containing compound (Zr(OH) 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0165] Embodiment 11

[0166] In addition to further mixing 0.1 mol % of a zirconium-containing compound (ZrO 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0167] Example 12

[0168] In addition to further mixing 0.2 mol% of the zirconium-containing compound (ZrO 2 ) was followed by a first heat treatment at 770° C., and the rest was carried out in the same manner as in Example 1 to prepare a positive electrode active material.

[0169] Embodiment 13

[0170] In the NiCoMn(OH) prepared by coprecipitation reaction 2 (d(50) = 3.0 μm) and Li as a lithium compound 2 CO 3 After weighing and mixing LiOH (Li / M ratio = 1.05 ± 0.05) and 2.0 mol% KCl, a first heat treatment was performed at 770°C for 12 hours to prepare a Li 1.0 Ni 0.9 Co 0.078 Mn 0.022 O 2 The lithium-based composite oxide prepared above was added to distilled water and washed with water while maintaining the temperature. After the dehydration process, it was dried at 150° C. in a vacuum atmosphere. Next, the dried lithium-based composite oxide was subjected to a second heat treatment at 700° C. for 12 hours to obtain a positive electrode active material.

[0171] Embodiment 14

[0172] In addition to further mixing 1.0 mol% NH 4H 2 PO 4 A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment was performed at 770° C. after replacing 2.0 mol % of KCl.

[0173] Embodiment 15

[0174] A positive electrode active material was prepared in the same manner as in Example 1, except that 2.0 mol % of NaCl was further mixed before the first heat treatment in place of 2.0 mol % of KCl and then the first heat treatment was performed at 770° C.

[0175] Comparative Example 1

[0176] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 650°C.

[0177] Comparative Example 2

[0178] A positive electrode active material was prepared in the same manner as in Example 1, except that the first heat treatment temperature was 990°C.

[0179] Experimental Example 1. Structural Analysis of Positive Electrode Active Materials

[0180] (1) SEM photo analysis of positive electrode active materials

[0181] Figures 4 to 6 Cross-sectional SEM photographs of the positive electrode active materials according to Example 1, Example 2 and Comparative Example 1 are sequentially shown, that is, measurement results of the grain boundary density of the secondary particles contained in the positive electrode active materials are respectively shown.

[0182] Reference Figures 4 to 6 It can be confirmed that the positive electrode active materials according to Examples 1 and 2 have a larger ratio of secondary particles having a grain boundary density of 0.5 or less among the plurality of secondary particles constituting the positive electrode active materials than the positive electrode active material according to Comparative Example 1.

[0183] As described above, the greater the ratio of secondary particles with a grain boundary density of less than 0.5 among the multiple secondary particles constituting the positive electrode active material, the smaller the side reactions occurring on the grain boundary surfaces in the electrolyte and the secondary particles, and as the ratio of lithium ion diffusion paths in the long axis direction in the secondary particles increases, the lithium ion conductivity and electronic conductivity through the positive electrode active material can be improved.

[0184] Table 1 below shows the results of measuring the fraction of the grain boundary density of the secondary particles contained in the positive electrode active material prepared according to Preparation Example.

[0185] Table 1

[0186]

[0187] Figures 7 to 12 The SEM images of the positive electrode active materials according to Example 1, Example 3, Example 4, Example 5, Example 7 and Example 11 are shown respectively. Fig.13 and Fig.14 The SEM images of the positive electrode active materials according to Comparative Example 1 and Comparative Example 2 are respectively.

[0188] First, refer to Figures 7 to 10 It can be confirmed that as the first heat treatment temperature increases, the grain boundary density of the secondary particles decreases.

[0189] And, referring to the SEM photographs of the positive electrode active materials according to Example 7 and Example 11, respectively. Fig.11 and Fig.12 It can be confirmed that when preparing the lithium-based composite oxide, even if a flux is added, the ratio of secondary particles with a grain boundary density of 0.5 or less among the plurality of secondary particles constituting the above-mentioned positive electrode active material does not decrease much. In addition, it can be confirmed that although the first heat treatment temperature (770°C) in Examples 7 and 11 is lower than the first heat treatment temperature (800°C) in Example 1, the addition of a flux promotes particle growth, thereby presenting a grain boundary density fraction at a level similar to that of Example 1.

[0190] In contrast, referring to the SEM photograph of the positive electrode active material according to Comparative Example 1, Fig.13 , it can be confirmed that the positive electrode active material includes secondary particles with a relatively large grain boundary density, unlike the positive electrode active material according to the embodiment. Fig.14 , it can be confirmed that the positive electrode active material according to Comparative Example 2 includes secondary particles having a grain boundary density at a level similar to that of the embodiment.

[0191] (2) TEM photo analysis of positive electrode active materials

[0192] Figures 15 to 20 TEM photos of the positive electrode active materials according to Example 1, Example 3, Example 4, Example 5, Example 7 and Example 11 are shown in order, respectively. Fig.21 and Fig. 22 TEM images of the positive electrode active materials according to Comparative Example 1 and Comparative Example 2, respectively.

[0193] Reference Figures 15 to 18It can be confirmed that the cation mixed layer (rock salt structure) has a different crystal structure from the bulk (layered structure). In addition, it can be confirmed that as the ratio of secondary particles having a grain boundary density of 0.5 or less in the plurality of secondary particles constituting the positive electrode active material increases, the thickness of the cation mixed layer also tends to increase.

[0194] And, referring to TEM photographs showing the positive electrode active materials according to Example 7 and Example 11, respectively. Fig.19 and Fig. 20 It can be confirmed that when preparing the lithium-based composite oxide, even if the first heat treatment temperature is reduced compared with Example 1, the thickness of the cation mixed layer is increased by adding the flux.

[0195] On the other hand, referring to the TEM photograph of the positive electrode active material according to Comparative Example 1 Fig. 20 , it can be confirmed that, unlike the positive electrode active material according to the embodiment, the measured thickness of the cation mixed layer is too thin. Fig. 22 In the case of the positive electrode active material according to Comparative Example 2, it was confirmed that an excessively thick cation mixed layer was formed on the surface. As described above, an excessively thick cation mixed layer may reduce the electrical characteristics of the positive electrode active material.

[0196] The following Table 2 shows the average particle size of the primary particles and secondary particles included in the positive electrode active material prepared according to the preparation example, and the ratio of the thickness of the cation mixed layer formed on the surface of the primary particles and the secondary particles relative to the average particle size of the primary particles and the secondary particles.

[0197] Table 2

[0198]

[0199] x1: Average particle size of primary particles

[0200] d1: Thickness of the cation mixed layer present on the surface of the primary particle

[0201] x2: Average particle size of secondary particles

[0202] d2: Thickness of the cation mixed layer present on the surface of the secondary particle

[0203] Referring to Table 2, it can be confirmed that in the positive electrode active materials according to Examples 1 to 15, the ratio (d1 / x1) of the thickness (d1) of the cation mixing layer relative to the average particle size (x1) of the primary particles is greater than 0.0008 and less than 0.0052, and the ratio (d2 / x2) of the thickness (d2) of the cation mixing layer relative to the average particle size (x2) of the secondary particles is greater than 0.00014 and less than 0.00281. In addition, it can be confirmed that the ratio (d1 / d2) of the thickness (d1) of the cation mixing layer present on the surface of the primary particles and the thickness (d2) of the cation mixing layer present on the surface of the secondary particles is greater than 0.53 and less than 1.0.

[0204] As described above, in the positive electrode active material according to an embodiment of the present invention, by making the ratio (d1 / x1) of the thickness (d1) of the cation mixing layer relative to the average particle size (x1) of the primary particle, the ratio (d2 / x2) of the thickness (d2) of the cation mixing layer relative to the average particle size (x2) of the secondary particle, and the ratio (d1 / d2) of the thickness (d1) of the cation mixing layer present on the surface of the primary particle and the thickness (d2) of the cation mixing layer present on the surface of the secondary particle within the predetermined range as described above, the improved electrochemical characteristics and stability described below can be presented.

[0205] Furthermore, when comparing the positive electrode active materials according to Example 1 and Examples 6 to 15, when preparing the positive electrode active materials, the positive electrode active materials according to Examples 6 to 15 using a flux have a ratio (d1 / x1) of the thickness (d1) of the cation mixing layer relative to the average particle size (x1) of the primary particles and a ratio (d2 / x2) of the thickness (d2) of the cation mixing layer relative to the average particle size (x2) of the secondary particles, as compared to Example 1 without using a flux.

[0206] (3) XRD analysis of positive electrode active materials

[0207] By XRD analysis of the positive electrode active material prepared according to the preparation example, the Ni occupancy rate (Ni Li occupancy).

[0208] In XRD analysis, a Cu-Kα radiation source is used as the X-ray source. The measurement was performed by θ-2θ scanning (Bragg-Brentano parafocusing geometry) in the range of 10° to 120° (2θ) at a step size of 0.01°. The measurement results are shown in Table 3 below.

[0209] Table 3

[0210] Classification Ni Occ.(%) Example 1 1.36 Example 2 2.46 Example 3 4.3 Example 4 0.94 Example 5 1.07 Example 6 1.23 Example 7 1.38 Example 8 1.41 Example 9 1.37 Example 10 1.11 Embodiment 11 1.35 Example 12 1.54 Embodiment 13 2.76 Embodiment 14 2.11 Embodiment 15 2.48 Comparative Example 1 0.53 Comparative Example 2 6.44

[0211] Referring to Table 3, it can be confirmed that the occupancy of Ni inserted into the Li 3a site of the positive electrode active material has a tendency similar to the thicknesses d1 and d2 of the cation mixed layer shown in Table 2.

[0212] The Ni occupancy rate inserted into the Li 3a position of the positive electrode active materials according to Examples 1 to 15 is greater than 0.53% and less than 6.44%. The positive electrode active materials according to various embodiments of the present invention have a cation mixed layer of appropriate thickness on the surface of the primary particles and secondary particles constituting the above-mentioned positive electrode active materials, and present an appropriate level of Ni occupancy rate in the Li 3a position accordingly, so that the electrochemical characteristics and structural stability described below can be improved compared with the comparative examples.

[0213] Experimental Example 2. Measurement of electrochemical properties of positive electrode active materials

[0214] (1) Preparation of lithium secondary batteries

[0215] In order to confirm whether the positive electrode active material prepared according to the embodiment of the present invention exhibits electrochemical properties at the same or similar level as the existing positive electrode active material when a lithium secondary battery is prepared, in this experimental example, a lithium secondary battery suitable for a positive electrode prepared using the positive electrode active material prepared according to the embodiment and the comparative example is prepared.

[0216] The slurry was prepared by mixing the prepared positive electrode active material, super-P as a conductive agent, and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 92:4:4. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm and vacuum dried at 135°C to prepare a positive electrode for a lithium secondary battery.

[0217] The above positive electrode and lithium foil were used as counter electrodes, and a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and LiPF 6 A button cell was prepared according to a generally known production process using a liquid electrolyte solution having a concentration of 1.15 M dissolved in a solvent obtained by mixing ethylene carbonate and ethyl methyl carbonate at a volume ratio of 3:7.

[0218] (2) Evaluation of battery capacity and life characteristics of lithium secondary batteries

[0219] Using an electrochemical analyzer (Toyo, Toscat-3100), a charge / discharge experiment was carried out at 25°C, a voltage range of 3.0V to 4.25V, and a discharge rate of 0.5C to 4.0C to determine the initial charge capacity, initial discharge capacity, initial reversible efficiency characteristics, and rate characteristics of the lithium secondary battery prepared by the above method.

[0220] Furthermore, the lithium secondary battery prepared by the above method was charged and discharged 50 times at 1C / 1C under a driving voltage range of 3.0V to 4.25V at a temperature of 25°C, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention; capacity retention) was measured.

[0221] The measured battery capacity and life characteristics are shown in Tables 4 and 5 below.

[0222] Table 4

[0223]

[0224]

[0225] Table 5

[0226]

[0227] Referring to Table 4, it can be confirmed that relatively excellent levels of initial capacity and reversible efficiency are exhibited when using the positive electrode active materials according to Examples 1 to 15. In addition, when comparing the cases of using the positive electrode active materials according to Examples 1 and 7, it can be confirmed that the positive electrode active material according to Example 7 using a flux when preparing the positive electrode active material is slightly improved in initial capacity and reversible efficiency compared to the examples without using the flux.

[0228] On the other hand, the initial reversible efficiency of the positive electrode active material according to Comparative Example 2 is particularly low compared with other Examples and Comparative Examples, and thus it is found that the positive electrode active material is not actually suitable for use in a lithium secondary battery.

[0229] Furthermore, referring to Table 5, in the case of using the positive electrode active material according to the embodiment, the charge / discharge test results at a discharge rate of 0.5C to 4.0C were applied compared to the comparative example, and it can be confirmed that the rate characteristics and life characteristics are generally high. Furthermore, when comparing the cases of using the positive electrode active materials according to Example 1 and Example 7, it can be confirmed that the life characteristics of the positive electrode active material according to Example 7 using a flux when preparing the positive electrode active material are further improved compared to Example 1 in which no flux is used.

[0230] On the other hand, the positive electrode active material according to Comparative Example 1 has the lowest life characteristics compared with other Examples and Comparative Examples, and thus is not actually suitable for use as a positive electrode active material for a lithium secondary battery.

[0231] Example 3. Stability evaluation of positive electrode active materials and secondary batteries

[0232] (1) Thermal stability evaluation

[0233] In order to evaluate the thermal stability of the positive electrode active materials according to the examples and comparative examples, a thermogravimetric analyzer (TA Instruments, Q20) was used to increase the temperature from 25°C to 350°C at a heating rate of 10°C / min in an Ar atmosphere at normal pressure to measure the weight loss. The measurement results are shown in Table 6 below.

[0234] In the following Table 6, the onset temperature (on-set) refers to the onset temperature at which the weight loss (pyrolysis) peak of the positive electrode active material appears as a result of TGA analysis, and the maximum temperature (peak) refers to the temperature at which the weight loss (pyrolysis) peak reaches the highest point.

[0235] In the case of the positive electrode active materials according to the remaining examples except Example 4, Example 5 and Example 15, a weight loss peak appeared at a temperature of about 230° C. or more, and on the other hand, in the case of the positive electrode active materials according to Comparative Examples 1 and 2, a weight loss peak appeared at a temperature of about 225° C. or less. Among them, it can be confirmed that since the positive electrode active materials according to Examples 4, 5 and 15 have a weight loss peak at a temperature of about 225° C. or more, their high temperature stability is relatively high compared with the positive electrode active materials according to Comparative Examples 1 and 2.

[0236] On the other hand, it can be confirmed that the cathode active materials according to Examples 1 to 15 also have higher temperatures when the weight loss peak reaches the highest point than those according to Comparative Examples 1 and 2, and thus have relatively high high temperature stability.

[0237] Table 6

[0238]

[0239] (2) Preparation of lithium secondary batteries

[0240] In order to confirm whether a lithium secondary battery prepared using the positive electrode active materials according to the embodiments and comparative examples of the present invention can exhibit electrochemical properties at the same or similar level as those of existing positive electrode active materials, in this embodiment, a lithium secondary battery suitable for a positive electrode prepared using the positive electrode active materials prepared according to the embodiments and comparative examples is prepared.

[0241] The slurry was prepared by mixing the prepared positive electrode active material, super-P as a conductive agent, and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 92:4:4. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm and vacuum dried at 135°C to prepare a positive electrode for a lithium secondary battery.

[0242] The above positive electrode and lithium foil were used as counter electrodes, and a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and LiPF 6 A button cell was prepared according to a generally known production process using a liquid electrolyte solution having a concentration of 1.15 M dissolved in a solvent obtained by mixing ethylene carbonate and ethyl methyl carbonate at a volume ratio of 3:7.

[0243] (3) Measurement of gas generation from lithium secondary batteries

[0244] The lithium secondary battery prepared by the above method was charged to 4.25V at a constant current of 0.2C and then stored at 60°C for 14 days to measure the volume change of the lithium secondary battery due to gas generation in the lithium secondary battery. The volume change measurement results are shown in Table 7 below.

[0245] Table 7

[0246] Classification <![CDATA[Gas generation amount (Δcm 3 )]]> Example 1 0.027 Example 2 0.025 Example 3 0.018 Example 4 0.071 Example 5 0.033 Example 6 0.029 Example 7 0.019 Example 8 0.018 Example 9 0.03 Example 10 0.029 Embodiment 11 0.020 Example 12 0.017 Embodiment 13 0.045 Embodiment 14 0.044 Embodiment 15 0.029 Comparative Example 1 0.108 Comparative Example 2 0.017

[0247] Referring to Table 7, it can be confirmed that in the case of the lithium secondary batteries using the cathode active materials according to Examples 1 to 15 and Comparative Example 2, the amount of gas generation is reduced compared to the lithium secondary battery using the cathode active material according to Comparative Example 1.

[0248] When an overcurrent exceeding the limit flows through a lithium secondary battery, as the temperature inside the battery rises rapidly, it may cause a decomposition reaction of the electrolyte and generate gas. However, in this experimental example, the condition for overcurrent to flow through the lithium secondary battery is not met, so it can be expected that gas is generated due to side reactions between the interface and surface of the electrolyte and the positive electrode active material.

[0249] Considering the results of Table 7, it can be confirmed that the thermal stability and storage stability and the like of the cathode active materials according to Examples 1 to 15 based on structural stability are similar to or superior to those of existing cathode active materials.

[0250] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material comprising secondary particles formed by agglomerating a plurality of primary particles of a lithium-based composite oxide, The ratio x2 / x1 of the average particle size x2 of the secondary particles to the average particle size x1 of the primary particles is 1.9 or more and 10.3 or less, The Ni occupancy in the Li3a site obtained by Rietveld analysis of X-ray diffraction of the secondary particles is greater than 0.53% and less than 6.44%.

2. The positive electrode active material according to claim 1, wherein The cation mixed layer exists on the surface of the primary particles. A ratio d1 / x1 of the thickness d1 of the cation mixed layer to the average particle diameter x1 of the primary particles is greater than 0.0008 and less than 0.0052.

3. The positive electrode active material according to claim 2, wherein The thickness d1 of the cation mixed layer present on the surface of the primary particle is greater than 0.00023 μm and less than 0.01204 μm.

4. The positive electrode active material according to claim 2, wherein The cation mixed layer has a crystal structure selected from a layered structure, a rock salt structure, and a spinel structure.

5. The positive electrode active material according to claim 1, wherein The cation mixed layer exists on the surface of the secondary particles. A ratio d2 / x2 of a thickness d2 of the cation mixed layer to an average particle diameter x2 of the secondary particles is greater than 0.00014 and less than 0.00281.

6. The positive electrode active material according to claim 5, wherein The thickness d2 of the cation mixed layer present on the surface of the secondary particle is greater than 0.00043 μm and less than 0.01208 μm.

7. The positive electrode active material according to claim 5, wherein The cation mixed layer has a crystal structure selected from a layered structure, a rock salt structure, and a spinel structure.

8. The positive electrode active material according to claim 1, wherein The positive electrode active material is an aggregate of secondary particles having mutually different grain boundary densities: Grain boundary density = (number of interfaces between primary particles in secondary particles / number of primary particles constituting secondary particles).

9. The positive electrode active material according to claim 8, wherein The ratio of the secondary particles having a grain boundary density of 0.5 or less among the plurality of secondary particles constituting the positive electrode active material is 30% or more.

10. The positive electrode active material according to claim 9, wherein The ratio of secondary particles having a grain boundary density of 0.5 or less among the plurality of secondary particles constituting the positive electrode active material is less than 84%.

11. The positive electrode active material according to claim 1, wherein The positive electrode active material includes a first aggregate consisting of 1 or 2 primary particles, a second aggregate consisting of 3 to 6 primary particles, and a third aggregate consisting of 7 to 10 primary particles. in, The ratio of the first aggregates in the positive electrode active material is 30% or more.

12. The positive electrode active material according to claim 1, wherein The average particle size of the primary particles is 1.0 μm to 5.0 μm.

13. The positive electrode active material according to claim 1, wherein The secondary particles have an average particle size of 1.0 μm to 20.0 μm.

14. The positive electrode active material according to claim 1, wherein The above-mentioned positive electrode active material includes small secondary particles having an average particle size of 1.0 μm to 5.0 μm and large secondary particles having an average particle size of 10.0 μm to 20.0 μm.

15. The positive electrode active material according to claim 14, wherein The average particle size of the aggregate of the secondary particles in which the small secondary particles and the large secondary particles are mixed is 3.0 μm to 18.0 μm.

16. The positive electrode active material according to claim 1, wherein The lithium-based composite oxide is represented by the following chemical formula 1: [Chemical formula 1] Li a Ni 1-(b+c+d+e) Co b M1 c M2 d M3 e O f Wherein, M1 is Mn or Al, M2 and M3 are independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb and Zr, M1 to M3 are different metals from each other. 0.90≤a≤1.05, 0≤b≤0.20, 0≤c≤0.20, 0≤d≤0.05, 0≤e≤0.05, 1.0≤f≤2.

0.

17. The positive electrode active material according to claim 1, wherein When the above positive electrode active material is subjected to thermogravimetric analysis at a temperature increase rate of 10°C / min from 25°C to 350°C under an Ar atmosphere at normal pressure, the starting temperature of the weight loss peak is higher than 225°C.

18. The positive electrode active material according to claim 1, wherein When the above positive electrode active material was subjected to thermogravimetric analysis at a temperature increase rate of 10°C / min from 25°C to 350°C under normal pressure Ar atmosphere, the temperature at which the weight loss peak reached the highest point was higher than 232°C.

19. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 18.

20. A lithium secondary battery comprising the positive electrode according to claim 19.